DELIK ADAT DALAM PERSPEKTIF MASYARAKAT HUKUM ADAT KABUPATEN ROKAN HILIR - Erdiato Erdianto (Faculty of Law, Universitas Riau, 2021)
Customary law is original Indonesian law that is not written in the form of the Republic of Indonesia law, which contains religious elements. From this word, it can also be said that the Customary Criminal Law is original Indonesian law which is not written in the form of an invitation containing religious elements, followed and obeyed by the community continuously, from one generation to the next. Violation of the rules and regulations is seen as causing shocks in society. Therefore, for the offender who is given customary sanctions, the community corrects custom or customary obligations through their customary officials.The discussion on customary law (including criminal law / customary offenses) is closely related to the current condition of the prevailing law in Indonesia (ius constitutum) which has legal pluralism. Legal pluralism can be implemented as the existence of more than one legal system that is jointly in the same social field. In the area of legal pluralism, on the one hand there are State laws (laws), and on the other hand, unwritten people's laws (including customary law) are still alive and well in tune with the development of the indigenous peoples themselves. The people in Rokan Hilir Regency (Rohil) are known to be still strong in holding customary teachings, culture and have customary laws that need to be observed in enforcing Adat offenses. Adat Rokan Hilir developed and developed in the community.